2008
DOI: 10.1007/s10815-008-9219-0
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of the Toll-like receptor family in ovulation

Abstract: Introduction Ovulation is similar to an inflammatory response and is associated with increased production of prostaglandins as well as local growth regulatory factors. However, the expression and function of innate immune cell-related genes in non-immune cells within the ovary has been reported recently and provides a novel and important regulatory system during ovulation. Discussion Several members of the Toll-like receptor (TLR) surveillance system are expressed in granulosa cells and cumulus cells. These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 40 publications
1
48
0
1
Order By: Relevance
“…Most interesting of the 10 reproductive genes located at the very highly significantly associated QTL region on SSC14 for LN-PDR, TRAFD1 is one of the negative regulators for the Toll-like receptor signaling pathway. Although the Toll-like receptor signaling pathway is related to innate immunity, several recent studies have shown that this pathway is involved in ovulation, transport of oocytes in the oviduct and during fertilization (Mashima et al, 2005;Herath et al, 2007;Liu et al, 2008;.…”
Section: Discussionmentioning
confidence: 99%
“…Most interesting of the 10 reproductive genes located at the very highly significantly associated QTL region on SSC14 for LN-PDR, TRAFD1 is one of the negative regulators for the Toll-like receptor signaling pathway. Although the Toll-like receptor signaling pathway is related to innate immunity, several recent studies have shown that this pathway is involved in ovulation, transport of oocytes in the oviduct and during fertilization (Mashima et al, 2005;Herath et al, 2007;Liu et al, 2008;.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of genes frequently associated with innate immune responses, many potent cytokines, such as IL-6, and runt-related transcription factor 1 (RUNX1) and RUNX2 are also impaired in mice lacking ERK1/2 (103,(115)(116)(117) (Figure 3). Recently, IL-6 alone has been shown to stimulate COC expansion and induce the expression of specific genes encoding proteins involved in this process (115).…”
Section: New Insights Into Factors Controlling Ovulation and Luteinizmentioning
confidence: 99%
“…adaptive) immune response (Medzhitov et al 1997, Takeda & Akira 2005. Moreover, multiple reports of TLRs in non-immune tissues have begun to surface, bringing to light non-immune-related functions of these PRRs (Liu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, recent reports have implied a role for TLR signaling in the regulation of vertebrate ovarian function (Shimada et al 2006, Herath et al 2007, Subdei et al 2007, Liu et al 2008. TLRs have been identified in ovarian cells from multiple species (murine, bovine, chicken), and have been shown in bovine and murine granulosa cells to functionally mediate steroidogenesis and pathogen phagocytosis respectively (Herath et al 2007, Shimada et al 2006.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation